1998
DOI: 10.1016/s0022-5347(01)64036-9
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Repair of Iatrogenic Injury to the Vas Deferens

Abstract: Pediatric inguinal hernia repair is the most common cause of iatrogenic injury to the vas deferens. Results of treatment of iatrogenic injury to the vas deferens are somewhat lower than for patients with obstructive azoospermia due to vasectomy. Iatrogenic injuries are associated with longer vasal defects, impaired blood supply and longer obstructive intervals frequently resulting in secondary epididymal obstruction. Crossover reconstruction is particularly useful when contralateral testicular atrophy is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(69 citation statements)
references
References 9 publications
1
62
0
6
Order By: Relevance
“…In the most common scenario, an unrecognized injury is revealed only years later in the evaluation of subfertile or azoospermic men who underwent hernia repair during childhood. 7,[9][10][11] Unlike in adults, inguinal hernia repair in children is the most common cause of injury to the vas deferens, 9 which is more delicate and attenuated in infants. Early reports suggested that vasal injury occurs in 0.8% to 2% of pediatric hernia cases.…”
Section: Discussionmentioning
confidence: 99%
“…In the most common scenario, an unrecognized injury is revealed only years later in the evaluation of subfertile or azoospermic men who underwent hernia repair during childhood. 7,[9][10][11] Unlike in adults, inguinal hernia repair in children is the most common cause of injury to the vas deferens, 9 which is more delicate and attenuated in infants. Early reports suggested that vasal injury occurs in 0.8% to 2% of pediatric hernia cases.…”
Section: Discussionmentioning
confidence: 99%
“…Due to a variety of factors, most commonly divorce and remarriage, 3% to 8% of vasectomized men request reversal [99,100]. Injury to the vas is also a common cause of obstruction, most often the result of childhood hernia repair, orchiopexy, or hydrocelectomy [101].…”
Section: Obstructionmentioning
confidence: 99%
“…18 However, epididymal blockage is not uncommonly found, due to either clinically obvious or clinically unrecognized epididymitis and, on rare occasions, due to Young's syndrome. [19][20][21] Prior hernia repair or pelvic surgery may be the inciting event in vasal injury. The histories, therefore, of epididymitis, hernia repair, scrotal surgery, chronic bronchitis, etc.…”
Section: The Medical and Surgical History: What Clues Might It Reveal?mentioning
confidence: 99%
“…It is important to be aware that the reference ranges of commercial kits are not based on the analysis of normozoospermic fertile men, but on the general population with different reproductive and age characteristics. The most accurate 'normal' value is based on the median FSH levels measured in normozoospermic men and corresponds to 1.5-8 IU l 21 . As spermatogenesis deteriorates and Sertoli cell output of inhibin wanes, there is a compensatory rise in pituitary elaboration of FSH such that the serum value ascends above the lower aspect of the 'reference range'.…”
Section: Hormonal Studies: Which Ones Should Be Ordered and How Do Thmentioning
confidence: 99%